EFFECT OF MULTI-INTENSITY OVERLOAD TRAINING TO IMPROVE OFFENSIVE PERFORMANCE EFFICIENCY IN WRESTLERS - Razzaq, Tawheed Haider Abdul (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. Defined as the lack of offensive efficiency during matches among Greco-Roman wrestlers. The need to use a multi-intensity overload training method to address this weakness. Research Objectives to determining the effectiveness of the training program in developing the speed and accuracy of executing offensive holds. Identifying the effect of multi-intensity overload training on improving offensive performance efficiency in Greco-Roman wrestlers. Objectives. This study aimed to detect intensity overload training on improving offensive performance efficiency of Greco-Roman wrestlers. Method. The researcher used an experimental design with a single group and pre- and post-tests on a sample of eight wrestlers from Damouk Sports Club. A training program was implemented for eight weeks, consisting of three training sessions per week, for a total of 24 sessions. Results. This study relied on three tests to measure offensive performance efficiency accuracy of execution of offensive holds, speed of execution of hold, and the number of successful offensive holds. Pre-tests were administered before program, and post-tests were administered after its completion. Results showed statistically significant differences between pre- and post-tests, favoring post-tests in all variables, indicating effectiveness of training program. Conclusion. The researcher concluded that multi-intensity overload training contributed to improving efficiency of offensive performance in terms of accuracy, speed and number of successful holds, as well as improving wrestlers' ability to perform under conditions of varying physical exertion.